Gymnosperms of Sikkim, India - Srivastava, R.C (Asia life sciences :the international journal of life sciences., 1993)
"A brief taxonomic account of 24 species in 18 genera belonging to 10 families of Gymnosperms found in Sikkim, India is presented. Keys to the families, genera and species as well as vernacular names, ways of propagation, distribution and uses of each taxon are also provident."